Bayberry tannin immobilized bovine serum albumin nanospheres: characterization, irradiation stability and selective removal of uranyl ions from radioactive wastewater. Issue 31 (25th July 2018) - Yu, Jie; Luo, Xuegang; Liu, Bo; Zhou, Jian; Feng, Jian; Zhu, Wenkun; Wang, Shanlin; Zhang, Yongde; Lin, Xiaoyan; Chen, Ping
Abstract : A novel bayberry tannin immobilized BSA–BT-NS adsorbent with excellent adsorption capacity and high selectivity for UO2 2+ . Abstract : With the widespread use of nuclear energy, uranium containing radioactive waste water has raised global concerns on environmental sustainability, calling for high-performance materials in effective pollution treatments. Here, a novel adsorbent was prepared by immobilizing bayberry tannin onto bovine serum albumin nanospheres (BSA–BT-NSs), which was shaped by antisolvent method. The as-prepared adsorbent was characterized by SEM, TEM, FT-IR, and XPS, and showed excellent adsorption capacity and high selective adsorption for uranyl ions (UO2 2+ ) from radioactive wastewater, which included Fe 3+, Mn 2+, Cs 2+, Co 2+, and Sr 2+ . The effects of different adsorption parameters such as pH, temperature, time, and initial UO2 2+ concentration were investigated. The adsorption isothermal data were well fitted by the Langmuir isotherm model, and a maximum adsorption capacity of 487.805 mg g −1 was estimated. Furthermore, the BSA–BT-NSs possess excellent stability under 60 Co γ-ray irradiation at total doses ranging from 10 kGy to 350 kGy. These facts indicated that BSA–BT-NSs could be used as a low-cost and environmentally friendly adsorbent for UO2 2+ removal with high efficiency and selectivity from various uranium-containing radioactive industrial effluents. More importantly, combined with the characterization analysis, adsorption experimental results, and theory calculations based on density functional theory, the adsorption mechanism of the BSA–BT-NSs is revealed.